Regime Shifts in the North Pacific Simulated by a COADS-driven Isopycnal Model - 王佳 吴立新 刘征宇 王东晓 (Advances in atmospheric sciences, 2003)
The Miami Isopycnal Coordinate Ocean Model (MICOM) is adopted to simulate the interdecadal variability in the Pacific Ocean with most emphasis on regime shifts in the North Pacific. The compu-tational domain covers 60°N to 40°S with an enclosed boundary condition for momentum flux, whereas there are thermohaline fluxes across the southern end as a restoring term. In addition, sea surface salinity of the model relaxes to the climatological season cycle, which results in climatological fresh water fluxes.Surface forcing functions from January 1945 through December 1993 are derived from the Comprehensive Ocean and Atmospheric Data Set (COADS). Such a numerical experiment reproduces the observed evo-lution of the interdecadal variability in the heat content over the upper 400-m layer by a two-year lag.Subduction that occurs at the ventilated thermocline in the central North Pacific is also been simulated and the subducted signals propagate from 35°N to 25°N, taking about 8 to 10 years, in agreement with the eXpendable Bathy Thermograph observation over recent decades. Interdecadal signals take a southwest-ward and downward path rather than westward propagation, meaning they are less associated with the baroclinic planetary waves. During travel, the signals appear to conserve potential vorticity. Therefore,the ventilated thermocline and related subduction are probably the fundamental physics for interdecadal variability in the mid-latitude subtropics of the North Pacific.